Critical Thinking Skill Seen from Curiosity on Independent Learning Assisted by Module - Nafisa, Dian; sukestiyarno, YL; Hidayah, Isti (Unnes Journal of Mathematics Education Research, 2021)
This research aims to describe critical thinking skill of students seen from curiosity on independent learning assisted by module. This mix method research used sequential explanatory design. The data collection was done through observation, test, and interview techniques. The subjects were seventh graders. The quantitative data was selected by purposive sampling technique. The qualitative data was based on the students’ curiosity levels: high, moderate, and low. The findings showed that independent learning assisted by module was qualified. It was shown on planning stage of learning instrument validation result. It met validity categories. The promoting stage showed 77.2%. The evaluation stage was done through individual accomplishment test. It obtained tcount= 6.34 > 1.69. The classical accomplishment zcount = 0.47 > 0.18. The proportional difference test showed that zcount = 2.88 > 0.112. The N-gain test showed 97.3%, experiencing improvement. The variance test obtained sig 0.016 < 0.05. The descriptions of the students’ critical thinking skills seen from curiosities showed that they were varied. The high curiosity student reached high, moderate, and low critical thinking skill categories. The moderate curiosity students reached high, moderate, and low critical thinking skill categories. Meanwhile, the low curiosity students reached low critical thinking skill category.